School institution services in human rights perspective - Akmal; Atika Ulya A (International Conference on Education, Islamic Studies and Social Sciences Research)
The purpose of this study is to analyze the services of school institutions in the perspective of Human Rights. Factors that affect the service are: (1) creating leadership that performs basic tasks and functions (Tupoksi) with human rights or ASN (State Civil Apparatus) that is not working professionally (Abuse of Power) or lack of human resources, (2) negligence or omission, Violation by Ommision, and (3) incorrect institutional policy factors violating the regulation (Violation by commmision) of public services by school institutions. The research method used a quantitative approach. Location of State Senior High School of Padang with 16 principals and 400 educators and educational staff as population and 46 samples who become respondents. Data were collected through questionnaires that have been validated and processed through Path-Analysis techniques. The results of the study prove that all variables, namely two independent variables and one moderator variable studied showed significant relationship and influence on the dependent variable. Thus the hypothetical model that has been proven can be used as a model of the school institution service that has human rights perspective, can improve the performance of educators and education personnel on services provided by the school. The results of this study indicate that professional services, not neglect, and humane policies can be used as models of institutional services in the context of different school cultural values spatially, so have the reliability of the model. Besides, this model can also be used as a guideline for the implementation of basic tasks and functions of school institutions that have human rights in Indonesia.